1988
DOI: 10.1007/bf01993983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reconstituted renal Na+/H+ exchanger by calcium-dependent protein kinases

Abstract: Studies were performed to determine the effect of protein phosphorylation mediated by calcium-calmodulin-dependent multifunctional protein kinase II and calcium-phospholipid-dependent protein kinase on Na+/H+ exchange activity. Proteins from the apical membrane of the proximal tubule of the rabbit kidney were solubilized in octyl glucoside and incubated in phosphorylating solutions containing the protein kinase. 22Na+ uptake was determined subsequently after reconstitution of the proteins into proteoliposomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…The latter result contrasted with results of Weinman and co-workers (27), who demonstrated that calcium-calmodulin protein kinase II inhibited the activity ofthe reconstituted renal brush border Na+-H+ exchanger. The reasons for the differences observed are unclear but may be related to differences in preparations (intact tubule vs. reconstituted Na+-H+ exchanger).…”
Section: Resultscontrasting
confidence: 90%
“…The latter result contrasted with results of Weinman and co-workers (27), who demonstrated that calcium-calmodulin protein kinase II inhibited the activity ofthe reconstituted renal brush border Na+-H+ exchanger. The reasons for the differences observed are unclear but may be related to differences in preparations (intact tubule vs. reconstituted Na+-H+ exchanger).…”
Section: Resultscontrasting
confidence: 90%
“…The cDNA encodes a protein consisting of 358 amino acids with a calculated molecular mass of 38.6 kD. This predicted size is less than that suggested from prior studies using column chromatography and autoradiography of SDS-PAGE gels containing the cofactor phosphorylated by PKA (4)(5)(6)(7)12). To clarify this issue, cell-free translation studies were performed.…”
Section: Discussionmentioning
confidence: 93%
“…RT-PCR was performed initially using rabbit kidney RNA and oligonucleotide or random primers for reverse transcription. For the PCR reaction, the oligonucleotide sense primer, 5 '-GAAGCGCAGCAGCAGACGGGC-3', and antisense primer, 5 '-ACTGGAGAATCGGGCGGAGAGG-3', were used. These primers spanned the stop codon region of the cDNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present studies, for reasons not immediately apparent, the response to PTH in NHERF-1 Ϫ/Ϫ proximal tubule cells was variable and, in fact, some of the cultures showed significant stimulation of NHE3 activity. It is worth noting that some prior studies have suggested that the direct effect of activation of protein kinase C is to activate NHE3 (39). In this regard then, NHERF-1 knockout mice may prove valuable in sorting out potential regulatory processes affecting the relation between PTH receptor activation and NHE3 activity.…”
Section: Nhe3 and Npt2a Regulation In Nherf-1 ϫ/ϫ Proximal Tubule Cellsmentioning
confidence: 99%